Olivia and the fairy princesses - Falconer, Ian, 1959- (Atheneum Books for Young Readers, 2012)
"Olivia is having an identity crisis! There are too many ruffly, sparkly princesses around these days, and Olivia has had quite enough. She needs to stand out! She has to be special! What will she be? Join Olivia on a hilarious quest for individuality in this latest book of the OLIVIA series, and rest assured, you won't find THIS pig in pink!"--